Finding and using causal hotspots: a practice in the making - Apgar, Marina; Snijder, Mieke (Institute of Development Studies, 2021)
This is the second blog in our series ‘Lessons on using Contribution Analysis for impact evaluation’. In our first blog, we introduced Contribution Analysis (CA) as an overarching approach to theory-based evaluation and the idea of causal hotpots as a way to zoom in, unpack and make the hard choices of where to focus evaluation research. Identifying specific links in the theory of change (ToC) with specific evaluation questions enables you to then choose appropriate methods. We have applied the approach in diverse settings, testing how robust Contribution Analysis can really be. Here we walk you through an example.

Learning through and about Contribution Analysis for impact evaluation - Apgar, Marina; Ton, Giel (Institute of Development Studies, 2021)
Over the past five years, colleagues from the Centre for Development Impact (CDI) – a joint initiative between the Institute of Development Studies, Itad and University of East Anglia – have been innovating with and learning how to use Contribution Analysis as an overarching approach to impact evaluation. In this blog series, we share our learning and insights, some of them in raw emergent form, highlight the complexities, nuances, excitements, and challenges of embracing new ways of doing impact evaluation. We begin this series by sharing ideas about ‘causal hotspots’ that first surfaced as ‘aha’ moments in our collaboration on the CDI short course Contribution Analysis for Impact Evaluation – the moments when we found the ways and words to better articulate our ideas and help people navigate the messy realities of theory-based evaluation.